Desarrollo e implementación de un sistema experto para la evaluación del aprendizaje receptivo del idioma inglés: caso: estudiantes de la academia particular Fine Tuned English (Zamora) de edades entre 3 1 a 18 años. - Iñiguez Loján, Carlos Alfredo, Andrés Paúl Luna Majía (2016)
To start with, the following research work has analyzed the evaluation process made by Fine- Tuned Zamora Language Institute in a thoroughly way. This was based on create, correct and qualify a test or quiz according to the established format. In fact, this process has been automated with its main goal is to speed up and keep better control of information generated by each user interaction. In order to reach this automation software called MACOOL has been developed. Particularly, this software was designed with the ICONIX methodology. This was based on four phases. They are requirements analysis, preliminary design analysis, design, implementation, and testing. The MACOOL expert system is a web system developed on Ruby on Rails. Then, It was used as RUBY programming system. After that, it also used MySql as a data repository. In addition, the Sublime Text was also used as a code editor. Thanks to these, this expert system can be used at any Web browser Therefore, MACOOL registers and manages the whole process of management of system users: Administrator, Teachers, and Students may use features based on their role. Finally, two handbooks were made to explain step by step how every single task is made inside this system. This has a user and programmer´s handbook.